2020
DOI: 10.3390/ijms21197140
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Regulation and Function of microRNA as Important Players in the Transition of MDS to Secondary AML and Their Cross Talk to RNA-Binding Proteins

Abstract: Myelodysplastic syndromes (MDS), heterogeneous diseases of hematopoietic stem cells, exhibit a significant risk of progression to secondary acute myeloid leukemia (sAML) that are typically accompanied by MDS-related changes and therefore significantly differ to de novo acute myeloid leukemia (AML). Within these disorders, the spectrum of cytogenetic alterations and oncogenic mutations, the extent of a predisposing defective osteohematopoietic niche, and the irregularity of the tumor microenvironment is highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 208 publications
0
18
0
Order By: Relevance
“…N6-methyladenosine (m6A) is the most abundant post-transcriptional mRNA modification and regulates the alternative splicing, localization, and stability of mRNAs, therefore influencing the level of subsequent protein expression (Huang et al, 2020). m6A modification of mRNAs is dynamically regulated by m6A RNA methylation regulators, including methyltransferases (METTL3, METTL14, METTL16, and WTAP), demethylases (FTO and ALKBH5), and binding proteins (YTH-domain containing proteins, HNRNP, and IGF2BP1-3) (Bauer et al, 2020). Studies have shown that aberrant regulation of m6A modification of mRNAs contributes to the development of lung cancer (Zhu et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…N6-methyladenosine (m6A) is the most abundant post-transcriptional mRNA modification and regulates the alternative splicing, localization, and stability of mRNAs, therefore influencing the level of subsequent protein expression (Huang et al, 2020). m6A modification of mRNAs is dynamically regulated by m6A RNA methylation regulators, including methyltransferases (METTL3, METTL14, METTL16, and WTAP), demethylases (FTO and ALKBH5), and binding proteins (YTH-domain containing proteins, HNRNP, and IGF2BP1-3) (Bauer et al, 2020). Studies have shown that aberrant regulation of m6A modification of mRNAs contributes to the development of lung cancer (Zhu et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of MDS, several genetic, immunologic as well as environmental factors have been shown to play a role in the pathophysiology of this disease, recent evidence suggest that immune dysregulation is a central feature of MDS and linked to disease initiation and progression to sAML [ 29 , 30 ]. So far, most studies analyzed the influence of the innate immune response [ 16 ], in particular the role of impaired Toll-like receptor (TLR) signaling pathways due to overexpression and/or mutations in immune related genes and microRNAs [ 30 , 31 ]. Furthermore, a high frequency of mutations in DNMT3A, TET2, ASXL1, and splicing factors, frequently identified in MDS and sAML, can influence the innate immune signaling and promote NF-κB signaling through various mechanisms [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A consensus on different miRNA profiles of MDS patients versus healthy controls or in patients who underwent leukemic transformation has not been reached. This is mainly due to the different techniques used for miRNA isolation and analysis, and to the different cell sources, which include BM mononuclear cells, total BM aspirate, BM MSC, total blood plasma, with only few studies having used CD34 + HSPCs, as recently reviewed (Bauer et al, 2020 ). Therefore, in addition to the technical differences in the various studies, most authors have profiled very heterogeneous samples, and it is hard to extrapolate which miRNA plays a role in MDS stem cells, also considering that no data have been reported on purified HSCs from MDS patients.…”
Section: Mirnas Hscs and Hema...mentioning
confidence: 99%